On the nature of the newly discovered Ω states. (24th August 2017) - Agaev, S. S.; Azizi, K.; Sundu, H.
Abstract: The mass and residue of the ground-state, as well as the first orbital and radial excitations of the heavy baryons with Q being b or c quark, for both and are calculated by means of the QCD two-point sum rule method using the general forms for the interpolating currents. In the calculations the quark, gluon and mixed vacuum condensates up to ten dimensions are taken into account. We compare our results for the masses of and baryons with the existing predictions of other theoretical works. Our results for the charmed baryons are confronted with the experimental data of the LHCb Collaboration to understand the nature of the recently observed narrow resonances. The predictions for the masses of the baryons with the same quantum numbers may shed light on future experimental searches for the corresponding bottom baryons.